1981
DOI: 10.1029/ja086ia11p09137
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic control of the winter anomaly in absorption of radio waves at mid‐latitudes

Abstract: Morphological features of the winter anomaly in radio wave absorption, i.e. anomalous and large excessive absorptions of MF and HF waves occuring on groups of winter days at mid-latitudes, are examined based on absorption data sets of MF waves at three ionospheric stations and fmin data sets at 35 stations in the northern and southern hemispheres. It is found that the winter anomaly occurs simultaneously in an extensive daytime area, at least scatteringly, mostly several hours to 1-3 days following the onset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…The Irkutsk plot has delays which are as long as 10 days. Sato (1981) was able to measure absorption at stations as equatorward as Wakkanai. Wakkanai and Brisbane (which have similar latitudes) have been investigated for delayed absorption by a method similar to that for Christchurch and Irkutsk.…”
Section: D-region Absorptionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Irkutsk plot has delays which are as long as 10 days. Sato (1981) was able to measure absorption at stations as equatorward as Wakkanai. Wakkanai and Brisbane (which have similar latitudes) have been investigated for delayed absorption by a method similar to that for Christchurch and Irkutsk.…”
Section: D-region Absorptionmentioning
confidence: 99%
“…One proposal has suggested that AGWs and related MS-TIDs are generated as a result of some of the D-region precipitation events responsible for the absorption (Bowman, 2000). Sato (1981) investigated this delayed absorption over a range of stations and detailed the literature on the subject. One result (Sato, 1981), which is relevant here, indicated the measurement of absorption of "-long duration, sometimes more than a fortnight".…”
Section: D-region Absorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The generation mechanisms of winter anomaly are still controversial (e.g., OFFERMANN, 1979;SATO, 1981). OGAWA et al (1992) have reported the winter anomaly over Japan during the DYANA campaign in 1990.…”
Section: Introductionmentioning
confidence: 99%